Anise essential oil immobilized in chitosan microparticles: a novel bactericidal material for food protection - Mendes, Carolina Rosai [UNESP]; Zortea, Antonella Valentina Lazzari; de Souza Laurentino, Gabriel; de Lima, Guilherme Henrique Teixeira; de Freitas, Pietro Luis Coletti Casemiro; Dilarri, Guilherme; Bidoia, Ederio Dino [UNESP]; Montagnolli, Renato Nallin (Springer Nature, 2024)
Foodborne infections in humans are one of the major concerns of the food industries, especially for minimally processed foods (MPF). Thereby, the packaging industry applies free chlorine in the sanitization process, ensuring the elimination of any fecal coliforms or pathogenic microorganisms. However, free chlorine’s propensity to react with organic matter, forming toxic compounds such as trihalomethanes and haloacetic acid. Therefore, the present work aimed to synthesize a novel organic biomaterial as an alternative to free chlorine. Chitosan microparticles were produced, with Pimpinella anisum (anise) essential oil immobilized in the biopolymer matrix (MPsQTO). The characterization of this biomaterial was done through GC–MS/MS, FT-IR, and SEM. Antimicrobial assays proved that the MPsQTO presented antibacterial activity for Escherichia coli, Salmonella typhi, Pseudomonas aeruginosa, and Bacillus subtilis at 300 µL mL−1 of concentration. The fluorescence microscope also showed the MPsQTO targets the cytoplasmatic membrane, which is responsible for cell death in the first minutes of contact. Studies with the mutant B. subtilis (amy
Keywords: Food safety; GC–MS/MS; Packinghouse; Pathogen microorganisms; Pimpinella anisum; Sanitization